2019
DOI: 10.3847/1538-3881/aaf56b
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Transit Spectroscopy of Warm Saturns

Abstract: We present high-resolution optical transmission spectroscopy of two sub-Saturn mass transiting exoplanets, HAT-P-12b and WASP-69b. With relatively low densities and high atmospheric scale heights, these planets are particularly well-suited to characterization through transit spectroscopy, and serve as ideal candidates for extending previously-tested methods to lower planetary masses. Using a single transit for each planet, we take advantage of the Doppler cross-correlation technique to search for sodium, potas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Although the LBT results indicate a nondetection of potassium, we cannot confidentially rule out the existence of a weak K feature, considering the large errors of the light curves acquired with narrow spectral bins and the effect of telluric oxygen absorption adjacent to the K absorption lines. Deibert et al (2019) observed the transit of HAT-P-12b with the echelle high-dispersion spectrograph mounted on the Subaru telescope. These authors achieved a 3.2 σ detection of sodium absorption.…”
Section: Comparison With Hst Results In the Visiblementioning
confidence: 99%
See 1 more Smart Citation
“…Although the LBT results indicate a nondetection of potassium, we cannot confidentially rule out the existence of a weak K feature, considering the large errors of the light curves acquired with narrow spectral bins and the effect of telluric oxygen absorption adjacent to the K absorption lines. Deibert et al (2019) observed the transit of HAT-P-12b with the echelle high-dispersion spectrograph mounted on the Subaru telescope. These authors achieved a 3.2 σ detection of sodium absorption.…”
Section: Comparison With Hst Results In the Visiblementioning
confidence: 99%
“…Sing et al (2016) obtained the optical transmission spectrum of the planet using the Space Telescope Imaging Spectrograph (STIS) mounted on HST and discovered a Rayleigh-scattering feature as well as indications for K absorption. Deibert et al (2019) reported a tentative detection of Na with the high-dispersion spectrograph mounted on the Subaru telescope, but they were not able to detect the K feature. Alexoudi et al (2018 reanalyzed the optical HST data to investigate a discrepancy of the S2016 result compared to a previously published ground-based broadband transmission spectrum of HAT-P-12b, which did not show a slope (Mallonn et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We then calculated the 1σ and 3σ detection limits using the phaseshuffling method (e.g. Esteves et al 2017;Deibert et al 2019). This is done by assigning random in-transit phases to the total CCF during the transit then integrating them at the planetary rest frame by adopting the K p of the detected signal.…”
Section: Non-detection Of Other Thermal Inversion Agentsmentioning
confidence: 99%
“…Using WFC3 on the HST, the planet was found to have a muted water feature at 1.4 µm with an overlying slope of a larger planet radius toward bluer wavelengths (Tsiaras et al 2018). Furthermore, absorption in Na D was detected during transit using high-resolution observations obtained with the HARPS spectrograph (Casasayas- Barris et al 2017), although an independent study using ESPaDOnS/CFHT could not confirm the sodium detection (Deibert et al 2019). This paper is organized as follows.…”
Section: Starmentioning
confidence: 99%